2011
DOI: 10.1016/j.ajic.2011.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Room ventilation and the risk of airborne infection transmission in 3 health care settings within a large teaching hospital

Abstract: Given the absence of definitive ventilation guidelines for hospitals, air-exchange measurements combined with modeling afford a useful means of assessing, on a case-by-case basis, the suitability of room ventilation for preventing airborne disease transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 24 publications
3
66
0
1
Order By: Relevance
“…These results were found at locations both directly in front of the coughing simulator and away from the initial cough aerosol plume, suggesting that exposure to the cough aerosol would occur anywhere in the room. This is consistent with modeling results reported by Knibbs et al, (28) although they and other authors also found that the configuration and direction of the ventilation system, and other factors, can have a large impact on exposure and that these factors are difficult to predict and control. (17,29,30) In a similar manner to the time scale discussion above, our results show that ventilation has a much greater effect on exposure over the long term than in the short period immediately after a cough.…”
Section: Discussionsupporting
confidence: 82%
“…These results were found at locations both directly in front of the coughing simulator and away from the initial cough aerosol plume, suggesting that exposure to the cough aerosol would occur anywhere in the room. This is consistent with modeling results reported by Knibbs et al, (28) although they and other authors also found that the configuration and direction of the ventilation system, and other factors, can have a large impact on exposure and that these factors are difficult to predict and control. (17,29,30) In a similar manner to the time scale discussion above, our results show that ventilation has a much greater effect on exposure over the long term than in the short period immediately after a cough.…”
Section: Discussionsupporting
confidence: 82%
“…Among indoor environments where bioaerosols are considered a problem, hospitals are of major concern as in these environments there are a wide range of people such as hospital and medical staff, service users, patients and visitors who can contact bioaerosols and inhale them (11,12). Therefore, the presence of excess bioaerosol in hospitals air can be a serious health threat (13). Perdelli et al (14) studied fungi load in different wards of a hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted under full scale conditions [12][13][14][15], within laboratory test facilities [16][17][18] and more recently through computational simulation [19][20][21][22][23][24][25][26][27] have all improved the understanding of infection risk which is directly influencing building design and ventilation guidance.…”
Section: Introductionmentioning
confidence: 99%